Urgensitas Kepribadian Da`i Dalam Berdakwah - Ngadri Yusro (Jurnal Dakwah dan Komunikasi, 2017)
The da'i can gain knowledge about theories of personality and dakwah, and they can learn the skills of diagnosis, interviews and various techniques, dakwah approach. What is brought by da'i in dakwah work is ultimately itself as a person. The da'i bring their life experiences into relationships with mad`u. The da'i, the muballigh, the religious counselor may be able to master the theories and techniques of dakwah but are not able to become da'i or counselor who adequate, until they become therapeutic individuals. To become therapeutic individuals for others, da'i must first be therapeutic for themselves. Being a therapeutic person implies a willingness to openly explore the facets of the life of da'i himself, then try to be the ones who fit the da'i's ability. This does not mean that the preacher does not have to have something to ask other than himself, for his knowledge of the dynamics of behavior and the ability to preach is also very important. This paper is based on the writer's belief that the personality of da'i is the main capital of dakwah success, but it can also be the biggest obstacle for his efforts to move change. Thus, the author's next description reveals certain assumptions related to the personality of da'i. An important part of this paper includes, da'i as a person, the personality of da'i in relation to Mad'u, and the skill of the da'i as the religious instructor.